THE COMPARATIVE PALEOGEODYNAMICAL CHARACTERISTIC OF GRANITOIDS OF EASTERN PRYAZOVYA OBTAINED WITH PETROPHYSICAL DATA - SHABATURA, O. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Based on complex analysis of petrophysical data is definite paleogeodynamical description of granitoids of East Pryazovya and picked out the main features of geodynamical regimes of zones tectonic-magmatic activization this region.